Hepatic mucinous cystadenoma: Cistoadenoma mucinoso hepático - Juárez Granda, Héctor (2019)
Hepatic cystadenoma is a very rare neoplasm, with less than 250 cases reported in the world literature, which occurs more frequently in women. Due to the difficulty of differentiating the simple cyst and the hydatid cyst with the hepatic cystadenoma; as well as its recurrence and possibility of dysplasia or carcinoma, if it is not treated by complete resection, we present the case of a woman of 56 years old with history of simple hepatic cyst treated on 2 occasions with simple hepatic cyst unroofing and that they relapsed, so it was a hepatic cystadenoma. DOI:10.25176/RFMH.v19.n2.2075